Application of Modified Silica Coated Magnetite Nanoparticles for Removal of Iodine from Water Samples - Madrakian, Tayyebeh; Afkhami, Abbas; Zolfigol, Mohammad Ali; Ahmadi, Mazaher; Koukabi, Nadia (Nano-Micro Letters, 2012)
The adsorption of iodine onto silica coated magnetite nanoparticles (im-SCMNPs) that modified with imidazole was investigated for removal of high concentrations of iodine from wastewater. Modified silica magnetite nanoparticles showed high efficiency in removing iodine from wastewater samples. The optimum pH for iodine removal was 7.0–8.0. The adsorption capacity was evaluated using both the Langmuir and Freundlich adsorption isotherm models. The size of the produced magnetite nanoparticles was determined by X-ray diffraction analysis and scanning electron microscopy. Synthesized magnetite nanoparticles showed the high adsorption capacity and would be a good method to increase adsorption efficiency for the removal of iodine in a wastewater treatment process. The Langmuir adsorption capacity (qmax) was found to be 140.84 mg/g of the adsorbent.